Between subversion to re-affirmation: homonormativism, homonationalism and male same-sex family. Issue 8 (17th November 2019) - Tsfati, Maya; Ben-Ari, Adital
ABSTRACT: This article focuses on Israeli male same-sex family, as a case study which provides an opportunity to understand the relationships between LGBT family, parenthood and the state. Based on the analysis of 39 in-depth semi-structured interviews with gay fathers, we show that although gay fathers use homonormative discourse they resist homonationalist ideology. This gap reflects the tension between compliance and subversion that shapes their experiences and accounts as well as their relationship with dominant ideology. The duality between acceptance and subversion enables the practise of subversion from within, thus revealing that subversion and compliance may co-exist. The co-existence of these categories offers an alternative to nationalistic ideology; trying to challenge it from within.